Respuesta :

Answer:

1/12

Step-by-step explanation:

Start by simplifying the fraction's signs:

[tex]-\frac{2}{3} - (- \frac{3}{4} ) = -\frac{2}{3} +\frac{3}{4}[/tex]

Now write both fractions as equivalent fraction with a common denominator of 12:

[tex]-\frac{2}{3} +\frac{3}{4} =-\frac{8}{12} +\frac{9}{12}=\frac{1}{12}[/tex]

If you need to add 5/6 to 5/12

again you need to write the fractions with a common denominator in this case also 12:

[tex]\frac{5}{6} +\frac{5}{12}= \frac{10}{12} +\frac{5}{12}=\frac{15}{12} = \frac{5}{4}[/tex]

in this last step we simplified a common factor of "3" in numerator and denominator to reduce the fraction to 5/4

The answer to this question is 1/12